Magnetic Resonance Imaging (MRI) Evaluation of Perianal Fistula with Surgical Correlation - Mian Waheed Ahmad, Hafiza Sameeya Shehzadi, Iqbal Hussain Dogar, Nawaz Rashid, M Azam Tayyab, Uzair Ahmed Qureshi, Rameez Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study's goal was evaluate the part magnetic resonance imaging plays in the identification and classification in perianal fistulas to contrast those results with those from surgery. Study Design: Cross Sectional Place & Duration: Study carried out between the periods of January 2022 to Aug 2022 Material & methods: This study was tested on 50 patients in the hospital. Patients who had undergone MRI pelvis with or without contrast study were counted in the current study. Patients who undergone surgery prior or had recurrent perianal illness were not included in the study. Short T1 inversion recovery, T2 weighted (T2W) sagittal, axial, and coronal MRI sequences (STIR), T1W axial, and coronal sequences, and T1W post contrast axial & coronal sequences were all evaluated. Results Reflected: while evaluation by MRI, among 50 patients, 45 which is 90% were man and 5 which is 10% were female gender. In 45 (90%) of the 50 patients overall, postoperative results confirmed perianal fistula. A total of 5(10%) patients had perianal sinus only. The primary tract was found to have a sensitivity and specificity of 97.73% and 83.33%, respectively, whereas the abscess had a sensitivity and specificity of 88.89% and 95.12%. High sensitivity was also acknowledged for accurately locating the internal opening (95.45%), detecting the horseshoeing (90.91%), correctly identifying the secondary ramification (92.86%) with specificity (94.44%). Conclusion: It is found that MRI demonstrated superior performance in evaluating perianal fistula with critical parameters (primary tract and its grading, internal opening, secondary ramification, abscess, horseshoeing). Pre-operative perianal fistula assessment should be correct to prevent problems and recurrence, which will decrease the need for additional surgeries. Practical Implication: As a result of this study, unnecessary radiation and diagnostic time could be avoided in the preoperative assessment of PAF in ano using MRI. It would also help decrease complications and unnecessary surgeries. Keywords: Magnetic Resonance Imaging and Perianal Fistula, perianal sinus, horseshoeing